Effectiveness of immunosuppressive therapy in children with autoimmune hepatitis and autoimmune sclerosing cholangitis - Dyba, M.B.; Berezenko, V.S.; Tkalyk , O.M.; Dmytrenko, Kh.Z. (Medicni Perspektivi, 2025)
Autoimmune liver diseases in children, particularly autoimmune hepatitis and autoimmune sclerosing cholangitis, represent a challenging clinical issue due to their variable clinical course, diagnostic complexity, and suboptimal therapeutic efficacy. Despite common pathogenetic mechanisms, including impaired immune regulation, association with class II major histocompatibility complex molecules, chronic inflammation, and fibrosis, these conditions differ significantly in clinical presentation, treatment response, and prognosis. The incidence of autoimmune hepatitis in children is 3-6 cases per 100,000, whereas autoimmune sclerosing cholangitis is rarer, diagnosed in 0.2-1.5 cases per 100,000 children. The primary therapeutic goal is achieving biochemical remission and preventing fibrosis progression. A lack of biochemical improvement within the first 6–12 months of treatment is associated with poorer outcomes; however, clear algorithms for intensifying therapy have not yet been established. Standardizing biochemical markers for assessing treatment effectiveness remains a relevant issue. The aim of this study was to perform a comparative analysis of immunosuppressive therapy effectiveness in children with autoimmune hepatitis and autoimmune sclerosing cholangitis based on the evaluation of biochemical response rates. We conducted a retrospective analysis of immunosuppressive therapy effectiveness during the first 12 months in children and adolescents with autoimmune liver diseases treated in the pediatric hepatology department for 2016 to 2024. Two groups were formed: group 1 – autoimmune hepatitis (n=84), and group 2 – autoimmune sclerosing cholangitis (n=38). At disease onset, children in group 2 exhibited higher gamma-glutamyltransferase levels (p=0.003) and more frequently had inflammatory bowel disease (68% vs. 9.5%, p<0.0001). Early biochemical response was achieved in 4 weeks of therapy in 86% of group 1 and 82% of group 2, respectively (p>0.05). In 6 months, complete biochemical response was observed in 50% of group 1 and 32% of group 2 (p=0.07). In 12 months, complete response rates were 73% and 47%, respectively (p=0.007). Elastography indicated a significant decrease in liver stiffness in both groups (p<0.0001 and p=0.002, respectively). Thus, children with autoimmune sclerosing cholangitis demonstrate significantly lower efficacy of immunosuppressive therapy within the first 12 months compared to autoimmune hepatitis. Liver stiffness measurement by elastography may serve as an additional objective criterion for evaluating treatment effectiveness.